Power systems modelling and fault analysis theory and practice - Tleis, Nasser D. (Newnes power engineering series., 2008)
This book provides a comprehensive practical treatment of the modelling of electrical power systems, and the theory and practice of fault analysis of power systems covering detailed and advanced theories as well as modern industry practices. The continuity and quality of electricity delivered safely and economically by todays and futures electrical power networks are important for both developed and developing economies. The correct modelling of power system equipment and correct fault analysis of electrical networks are pre-requisite to ensuring safety and they play a critical role in the identification of economic network investments. Environmental and economic factors require engineers to maximise the use of existing assets which in turn require accurate modelling and analysis techniques. The technology described in this book will always be required for the safe and economic design and operation of electrical power systems. The book describes relevant advances in industry such as in the areas of international standards developments, emerging new generation technologies such as wind turbine generators, fault current limiters, multi-phase fault analysis, measurement of equipment parameters, probabilistic short-circuit analysis and electrical interference. *A fully up-to-date guide to the analysis and practical troubleshooting of short-circuit faults in electricity utilities and industrial power systems *Covers generators, transformers, substations, overhead power lines and industrial systems with a focus on best-practice techniques, safety issues, power system planning and economics. *North American and British / European standards covered.